Penggunaan Media Gambar Pada Kemampuan Bercerita Siswa Kelas III SD Negeri Anggadita III - Tia Latifatu Sadiah (Jurnal Sekolah Dasar, 2019)
This study aims to determine the relationship between media images with the ability to tell stories of students on Indonesian subjects in Anggadita III Elementary School. This research is a type of qualitative research. Where the number of third grade students in Anggadita III Elementary School is 31 people and in this study the sample used was 3 students where 2 of them were students who were considered the most capable in telling stories while 1 other student who had storytelling skills was felt to be lacking . The collection technique in the study itself is to use through observation, interviews, and also documentation while the results of research and tests conducted using gamelan media have a considerable influence where of the 31 students only 5 people scored below 75. From the results of this study it can be concluded that image media can have an influence on students' storytelling abilities.